Factors Influencing Consumers’ Purchases of Snook (Centropomus viridis) and Red Snapper (Lutjanus peru) from Artisanal Aquaculture Cooperatives in Mexico - Marco Antonio Almendarez-Hernández; Ismael Sánchez-Brito; René Arturo Kachok-Gavarain; Deneb Maldonado-García; Carolina Sánchez-Verdugo; Minerva Concepción Maldonado-García (Fishes)
Aquaculture in developing countries, including Mexico, primarily consists of artisanal activities characterized by low-scale production. No studies in these regions has analyzed consumer preferences regarding aquaculture products, specifically for snook and red snapper. Consequently, to explore consumer preferences, the primary objective of this study is to estimate a measure of welfare in the form of willingness to pay (WTP) for fish cultivated under small-scale production conditions in floating cages. To examine the variables impacting WTP, we employed the random utility model (RUM) theoretical framework and a grouping of econometric models belonging to the discrete choice framework. The results strongly suggest that product attributes, such as presentation, purchasing location, consumption-related characteristics, and certain socioeconomic variables, significantly influence the decision to select farmed products. Developing productive aquaculture projects in Mexico and other developing countries can enhance community development by providing producers with accurate information for decision-making and by expanding the fish supply in response to the growing consumer demand.